Antimicrobial Resistance - A One Health Perspective 2021
DOI: 10.5772/intechopen.90891
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Titanium Dioxide Nanoparticles

Abstract: The widespread use of antibiotics has led to the emergence of multidrugresistant bacterial strains, and therefore a current concern for food safety and human health. The interest for new antimicrobial substances has been focused toward metal oxide nanoparticles. Specifically, titanium dioxide (TiO 2) has been considered as an attractive antimicrobial compound due to its photocatalytic nature and because it is a chemically stable, non-toxic, inexpensive, and Generally Recognized as Safe (GRAS) substance. Severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 77 publications
(63 reference statements)
0
85
0
2
Order By: Relevance
“…The crystalline structure and the shape of TiO2 NPs are both considered as the most important conditions that affect its physicochemical factors and therefore its antimicrobial activity [38]. The anatase crystalline structure of TiO2 presents its highest photocatalytic The crystalline structure and the shape of TiO 2 NPs are both considered as the most important conditions that affect its physicochemical factors and therefore its antimicrobial activity [38]. The anatase crystalline structure of TiO 2 presents its highest photocatalytic and antimicrobial activities among other crystalline structures.…”
Section: Resultsmentioning
confidence: 99%
“…The crystalline structure and the shape of TiO2 NPs are both considered as the most important conditions that affect its physicochemical factors and therefore its antimicrobial activity [38]. The anatase crystalline structure of TiO2 presents its highest photocatalytic The crystalline structure and the shape of TiO 2 NPs are both considered as the most important conditions that affect its physicochemical factors and therefore its antimicrobial activity [38]. The anatase crystalline structure of TiO 2 presents its highest photocatalytic and antimicrobial activities among other crystalline structures.…”
Section: Resultsmentioning
confidence: 99%
“…Gelover et al have shown the greater efficacy of photocatalysis with sol-gel-immobilized TiO 2 films over glass cylinders in inactivating both the total and faecal coliforms naturally present in spring water compared to solar disinfection (SODIS) [136]. As already reported for the other nanosized structures, the antibacterial activity of TiO 2 is closely related to nanoparticle properties such as size, morphology, and crystal nature, and also above all, because TiO 2 photocatalytic efficiency depends on them [141]. In this regard, TiO 2 nanotubes, thanks to their hollowed shape, gain a large surface area through which ROS can be generated; therefore, they possess a high antimicrobial activity [139].…”
Section: Gold Nanoparticlesmentioning
confidence: 88%
“…Similar to ZnO NPs, TiO 2 NPs have a wide band gap of 3.2 eV that can trigger the production of high-energy electron–hole pairs when exposed to UV light with wavelengths of 385 nm or lower [ 114 , 115 ]. Consequently, UV light irradiation leads to ROS production with high oxidative potential in the presence of oxygen [ 115 , 116 ]. As a result, ROS will cause DNA synthesis alteration, DNA and protein damage, and metabolic enzyme inactivation [ 114 , 117 , 118 ].…”
Section: Inorganic Nanoparticles With Antimicrobial Propertiesmentioning
confidence: 99%
“…The main factors influencing the antimicrobial properties of TiO 2 NPs are related to their morphology, size, crystal structure, and surface charge and chemistry, as well as their concentration and exposure time [ 114 , 115 , 117 , 119 ]. Additionally, the difference in the composition of the cell wall in Gram-positive and Gram-negative bacteria might also affect their antimicrobial bioactivity [ 118 ].…”
Section: Inorganic Nanoparticles With Antimicrobial Propertiesmentioning
confidence: 99%